PENGARUH MODAL BUDAYA, TINGKAT PENDIDIKAN ORANG TUA DAN TINGKAT PENDAPATAN ORANG TUA TERHADAP PRESTASI AKADEMIK PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - Henry Eryanto; Darma Rika Swaramarinda (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2013)
This research was aimed at describing the effect of cultural capital, education level of parents and income level of parents to academic achievement. In this research, the analysis use qualitative and quantitative. Qualitative analysis described in descriptive about cultural capital, education level of parents and income level of parents to academic achievement. The quantitative analysis used Logistic Regression. The Regression of research results show that: (1) cultural capital has a positive influence to academic achievement and the effect statistically significant. (2) education level of parents has a positive influence to academic achievement and the effect statistically significant. (3) income level of parents has a positive influence to academic achievement and the effect statistically significant.